THE EFFECT OF APPRAISAL AND REWARD SYSTEM, WORK HOURS, AND TIME PRESSURE, ON TURNOVER INTENTION THROUGH BURNOUT AS AN INTERVENING VARIABLE - Prabowo, Adia Adi; Nurhayati, Ida (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to determine the effect of the Appraisal and Reward System, Work Hours, and Time Pressure, on Turnover Intention through Burnout as an Intervening Variable. This research uses descriptive quantitative, then the population used in this study is employees who work in the Yogyakarta area with the number of samples obtained totaling 90 with saturated sampling techniques. The results of this study used PLS-SEM analysis by testing the measurement (Outer Model) and structural model (Inner Model). This study obtained the following results: appraisal and reward system negatively affect burnout and appraisal and reward system, work hours and time pressure negatively affect turnover intention, while burnout positively affects turnover intention and work hours and time pressure positively affects burnout. In addition, the appraisal and reward system has a negative and significant effect on turnover intention after burnout, while work hours and time pressure have a positive and significant effect on turnover intention after burnout. Keywords: Appraisal and Reward; Work Hours; Time Pressure; Turnover Intention; Burnout